설문지 분석법에 의한 氣虛 血虛 氣滯 陰虛 陽虛證의 표준 증상 및 남녀차이 연구 - 김강태(Kang Tae Kim); 엄현섭(Hyun Sup Eom); 이인선(In Seon Lee); 김종원(Jong Won Kim); 지규용(Gyoo Yong Chi) (동의생리병리학회지, 2006)
In order to establish the manifestational symptoms in men and women and highly frequent symptoms(HFS) of deficiency of Qi and blood(氣虛, 血虛), stagnation of Qi(氣滯), deficiency of Yin(陰虛), deficiency of Yang(陽虛) and , 546 questionaires were analyzed through Cronbach alpha value and Pearson's correlative efficient. Symptomatic differences of male and female specimens were as follows. HFS of Qi deficiency were similar in terms of inactivity like mental and physical fatigue, enervation in men and women. In blood deficiency, dizziness and light sleep were common in men and women, but mucosal symptoms of conjunctiva, lip, nail bed were more frequent in women than men. Emotional explosion was common in Qi stagnation, then women had more motivation-related symptoms than men. Inner heat was frequently arisen in Yin deficiency in both, and the heat was expressed more common in exterior and upper part in women but in interior abdominal part in men. In Yang deficiency, main symptoms of men were feeling coldness in peripheral, but Qi deficiency symptoms were more common in women former than coldness. KCI Citation Count: 4